Analisis Penggunaan Metode Saintifik dalam Peningkatan Keaktifan Peserta Didik - Ema Nur Fadilah; Siti Sri Wulandari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2021)
This research has the aim to describe of scientific methods in terms of increasing student activity. The study was classified as a qualitative descriptive study. The subjects used in this study were students of class X OTKP at Mojoagung Public Vocational School on Public Relations and Protocol. Data collection techniques used were observation and interviews. While data analysis techniques are used through several stages including data collection, data presentation and drawing conclusions. In the learning process students tend to be bored and less interested in the learning process that takes place because the method used is merely lecture and monotonous. Therefore this research was conducted so that students are more active in the learning process. The activeness of students in the learning process also has an important role in learning outcomes. The scientific learning model is a scientific approach and consists of several stages, including observing, asking questions, gathering information, reasoning, and communicating. Through these various stages students can increase their role in the learning process